Microbial Infections Are a Risk Factor for Neurodegenerative Diseases - Lotz, Sarah K.; Blackhurst, Britanie M.; Reagin, Katie L.; Funk, Kristen E. (Frontiers in Cellular Neuroscience, 2021)
Neurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis, comprise a family of disorders characterized by progressive loss of nervous system function. Neuroinflammation is increasingly recognized to be associated with many neurodegenerative diseases but whether it is a cause or consequence of the disease process is unclear. Of growing interest is the role of microbial infections in inciting degenerative neuroinflammatory responses and genetic factors that may regulate those responses. Microbial infections cause inflammation within the central nervous system through activation of brain-resident immune cells and infiltration of peripheral immune cells. These responses are necessary to protect the brain from lethal infections but may also induce neuropathological changes that lead to neurodegeneration. This review discusses the molecular and cellular mechanisms through which microbial infections may increase susceptibility to neurodegenerative diseases. Elucidating these mechanisms is critical for developing targeted therapeutic approaches that prevent the onset and slow the progression of neurodegenerative diseases.